Response of cyanobacteria to the fountain-based water aeration system in Jeziorak Mały urban lake - Zębek Elżbieta (Limnological Review, 2014)
This study of cyanobacteria phytoplankton was conducted from May to August in 2002, 2003 and 2005 during fountain-based water aeration in the pelagial of the Jeziorak Mały urban lake in Poland. Additional water mixing by this installation’s activity changed the cyanobacterial growth conditions. Although less of their proportion was noted in total phytoplankton abundance, higher mean abundance and biomass were recorded at the fountain than at the lake centre. Higher water temperature in the surface layer favoured cyanobacterial growth at the fountain, while higher iron concentration stimulated their development in the lake’s centre. This was supported by positive correlations between their abundance and these water parameters. Moreover, the fountain’s activity contributed to the cyanobacteria sinking in the water column. The higher abundance of cyanobacteria was found at 1m depth in May, July and August than in the fountain surface layer. Additional water mixing during fountain activity caused also a shift in their abundance maximum (C - June and F - August) and contributed to intensive organic matter decomposition. These conditions promoted cyanobacterial nutrient uptake from the water at the fountain, and this is supported by the negative correlation between their abundance and orthophosphate and total nitrogen concentrations. Generally, water mixing during the fountain’s activity does not inhibit the growth of cyanobacteria. This phenomenon disturbed abundance dynamics of the cyanobacteria in summer months but didn’t contribute to their abundance decrease. It is important for these results to be considered in future management of shallow urban lakes.